Characterization of geomagnetic parameters at different region / Rohana Abd Ghani - Abd Ghani, Rohana
Geographical factors theoretically affect geomagnetic field variation due to the exposure to the sun's activities. Previous scientist says that the region that being exposed to the sun light for a period of time will experienced to the high ultraviolet light. Earth's magnetic field is approximately a magnetic dipole, with the magnetic field S pole near the earth's geographic North Pole and the other magnetic field N pole near the earth's geographic South Pole. Earth magnetic data can be measured by magnetometer, Magnetic Data Acquisition System (MAGDAS) and by certain measurement. For this project, earth magnetic field from 3 different regions; Manado (Indonesia) for' equatorial region, Onagawa (Japan) for northern region and Cooktovvn (Australia) for southern region are chosen to be analyzed. The analysis is based on the different parameters of MAGDAS data focusing H, and Z parameters. From the analysis, the earth magnetic polar at different region can be mapped and defined. The results are useful to give the regional magnetic data and also give a significant contribution of a new knowledge on our earth magnetic activities that are closely related to the space activities. The data are supplied by Space Environment Research Centre (SERC), Kyushu University Japan. Both parameters are monitored for one month on January and April 2006. This factor also should be considered in designing the radio communication and propagation technologies.